1986
DOI: 10.1126/science.2418502
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cultures of HTLV-III—Infected T Cells: a Model of Cytopathology of T-Cell Depletion in AIDS

Abstract: Long-term cultures were established of HTLV-III-infected T4 cells from patients with the acquired immune deficiency syndrome (AIDS) and of T4 cells from normal donors after infection of the cells in vitro. By initially reducing the number of cells per milliliter of culture medium it was possible to grow the infected cells for 50 to 60 days. As with uninfected T cells, immunologic activation of the HTLV-III-infected cells with phytohemagglutinin led to patterns of gene expression typical of T-cell differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
211
1
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 517 publications
(214 citation statements)
references
References 22 publications
1
211
1
1
Order By: Relevance
“…Based on these observations, our experiments suggest that T cell activation may render the cell susceptible for HIV entry due to an increased expression of cell surface CD4. Indeed, previous studies have shown that activation of T cells strongly contributes to HIV replication (73)(74)(75)(76)(77). Up to now, however, these findings have been explained by an interplay of viral and host regulatory proteins, such as Tat, Rev, Nef, NF-B, and NF-AT.…”
Section: Discussionmentioning
confidence: 71%
“…Based on these observations, our experiments suggest that T cell activation may render the cell susceptible for HIV entry due to an increased expression of cell surface CD4. Indeed, previous studies have shown that activation of T cells strongly contributes to HIV replication (73)(74)(75)(76)(77). Up to now, however, these findings have been explained by an interplay of viral and host regulatory proteins, such as Tat, Rev, Nef, NF-B, and NF-AT.…”
Section: Discussionmentioning
confidence: 71%
“…The human immunodeficiency virus (HIV) infects helper T cells by binding the gpl20 virus envelope glycoprotein to CD4+ molecules (1). The selective infection and death of CD4+ T cells provides a simple explanation for the impairment of the immune system (2,3). This explanation, however, is widely debated (4)(5)(6)(7).…”
mentioning
confidence: 93%
“…One possibility is co-infection with other viruses, especially herpesviruses. Several studies have demonstrated the ability of secondary infectious agents to trigger HIV growth in vitro (Gendelman et al, 1986;Zagury et al, 1986;Mosca et al, 1987;Rando et al, 1987;Horvat et al, 1989). Clinical findings have served to focus attention on human cytomegalovirus (HCMV), an opportunistic pathogen that has been detected in a number of different immunodeficiency syndromes, including AIDS (Macher et al, 1983;Mintz et al, 1983) and HCMV viraemia parallels the progression of AIDS symptoms (Fiala et al, 1986).…”
Section: Introductionmentioning
confidence: 99%